PENGENALAN DAN PEMANFAATAN TUNGKU BIOMASA DENGAN PEMBAKARAN BERSIH BAGI PENGUSAHA IKAN KAYU (KEUMAMAH) DI KOTA BANDA ACEH - Hafidh Hasan; Sri Haryani Anwar (JUARA: Jurnal Wahana Abdimas Sejahtera, 2021)
Keumamah is made from the preservation of eastern little tuna (Euthynnus affinis). For keumamah production, boiling of fresh eastern little tuna in water, is one of the main process which requires a lot of energy. The keumamah producers utilize three-stone like stove with wood biomass as the fuel. The stove adoption is economically motivated since the fuel is cheaper than other form of commercial energy and relatively easy to obtain. However, the stove is inefficient and wasting the wood. Inefficient burning of wood releases smoke and volatile organic compounds (VOC) which are dangerous to human health and harmful for the environment. Therefore, in this community development program, two keumamah producers, located near Lampulo fish harbour - in Banda Aceh, were introduced to better practices in utilizing biomass wood as energy source. They were firstly given the information on the reverse impacts on health and environment introduced by three-stone like stove. The team has developed an improved biomass stove with improved efficiency, less fuel consumption and much cleaner combustion. Later this clean better design biomass stove with its advantages was introduced. From the test of performance, the stoves showed: 1) faster cooking time; 2) reduce fuel consumption by nearly 30%; 3) reduced smoke; and 4) flexible usage of working space with modular design. It is the intentions of this program for the stove to benefit the keumamah producers and their workers with less expending for fuel and cleaner work environment.